2012
DOI: 10.1002/zaac.201200128
|View full text |Cite
|
Sign up to set email alerts
|

On Tris(dithiocarbamato)‐Chromium(III), Cr(S2CNH2)3

Abstract: Scarab blue crystals of the title compound were precipitated from aqueous solutions of Cr III salts by adding an excess of ammoniumdithiocarbamate solution. The compound crystallizes in the trigonal space group R3 (No. 148) with a = 13.2694(8), c = 11.2542(7) Å and γ = 120°. The crystal structure consists of a three-dimensional hydrogen-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…118 These promising early findings have not been developed, although a 2012 paper briefly reported that [Cr(S 2 CNH 2 ) 3 ] decomposes above 215 °C, with PXRD showing the strongest reflections for rhombohedral Cr 2 S 3 , together with several additional reflections possibly originating from comparatively deficient sulfur phases. 119…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…118 These promising early findings have not been developed, although a 2012 paper briefly reported that [Cr(S 2 CNH 2 ) 3 ] decomposes above 215 °C, with PXRD showing the strongest reflections for rhombohedral Cr 2 S 3 , together with several additional reflections possibly originating from comparatively deficient sulfur phases. 119…”
Section: Groupmentioning
confidence: 99%
“…In 2000, Almond and co-workers reported that decomposition of [Cr­(S 2 CNEt 2 ) 3 ] between 255 and 450 °C in a low-pressure flow reactor gave layers of Cr 2 S 3 in either rhombohedral or trigonal forms . These promising early findings have not been developed, although a 2012 paper briefly reported that [Cr­(S 2 CNH 2 ) 3 ] decomposes above 215 °C, with PXRD showing the strongest reflections for rhombohedral Cr 2 S 3 , together with several additional reflections possibly originating from comparatively deficient sulfur phases …”
Section: Binary Sulfidesmentioning
confidence: 99%